El marketing online y la captación de clientes en la empresa industrial “Produplas - Cali Satan, Deysi Tatiana (2024)
ABSTRACT: The main objective of this present work is to demonstrate the importance of online marketing and customer acquisition in the industrial company Produplas. This strategy is crucial since it focuses on using digital media and online tools to promote the company's products and capture the attention of potential customers since through various strategies such as SEO (search engine optimization) it seeks to increase the visibility of Produplas and facilitate the rapid location of its products in search engines, which in turn contributes to attracting customers. The effective application of s EO can significantly improve the visibility of the company online, in addition for product advertising it will be considered in order to maximize the reach and expansion of Produplas products.